The effect of active recovery, massage and passive recovery on blood lactate concentration and swimming performance - Gowans, J.; Weston, A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Manual massage is routinely recommended and currently used in the preparation for exercise, recovering from exercise and as a method of enhancing performance. Many proponents state that massage augments lactate removal. These assumptions were tested by examining the effects of active recovery (A), massage (M) and passive recovery (P) on blood lactate and swimming performance. Swimming time, blood lactate (post warm up, 3 & 13 mins post both swims; YSI lactate analyser), heart rate and rate of perceived exertion (RPE) (post warm up, immediately & 3 mins post swims) were used to assess the performance. Twelve well trained, competitive swimmers participated in the study. Subjects swam one 200 m at a pace standardised to 90% of their current personal best, were subjected to one of the three 10 min recovery modes, then swam a 200 m maximal effort. Each subject completed all three recovery modalities on three separate occasions in a randomised order, balanced Latin square design. Group means were compared using analysis of variance and post-hoc testing. There was no significant difference between the mean times of the first swim (mean ± S.D) A: 147.0 ± 18.7; M: 146.4 ± 18.9; P: 147.0 ± 18.9 secs. The results indicate that active recovery resulted in a significantly greater blood lactate removal (75.0% decrease from post swim to post recovery intervention, p<0.05) when compared to massage (44.1% decrease) or passive recovery (56.4% decrease) which were not significantly different from each other. No significant difference was apparent in the subsequent maximal bout swim time, although there was a trend toward a faster mean swim time after an active recovery A: 142.6 ± 19.1; M: 143.1 ± 19.1; P: 144.5 ± 19.0. No differences in HR or RPE were apparent. The preliminary results of this study clearly indicate that a 10 min massage has no beneficial effect with respect to lactate removal. Furthermore, the results indicate that a low intensity active recovery or "swim down" is recommended for optimal lactate removal.